2013
DOI: 10.1155/2013/917198
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Differences in Systemic and Cell-Autonomous Immunity toL. monocytogenes

Abstract: Host defense against infection can broadly be categorized into systemic immunity and cell-autonomous immunity. Systemic immunity is crucial for all multicellular organisms, increasing in importance with increasing cellular complexity of the host. The systemic immune response to Listeria monocytogenes has been studied extensively in murine models; however, the clinical applicability of these findings to the human newborn remains incompletely understood. Furthermore, the ability to control infection at the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 169 publications
0
21
0
1
Order By: Relevance
“…During this early stages of life, neutrophils and monocytes together make up progressively less of the total WBC population, which correlates with susceptibility to Haemophilus influenzae pneumonia and otitis media (44,45). Interestingly, animal models have demonstrated that depleting neutrophils prior to pathogen inoculation can increase the pathogen burden, which has been shown for a Listeria monocytogenes disease model (46,47). Additionally, a depletion of monocytes can increase the risk of death from listerial infection (48).…”
Section: Figmentioning
confidence: 98%
“…During this early stages of life, neutrophils and monocytes together make up progressively less of the total WBC population, which correlates with susceptibility to Haemophilus influenzae pneumonia and otitis media (44,45). Interestingly, animal models have demonstrated that depleting neutrophils prior to pathogen inoculation can increase the pathogen burden, which has been shown for a Listeria monocytogenes disease model (46,47). Additionally, a depletion of monocytes can increase the risk of death from listerial infection (48).…”
Section: Figmentioning
confidence: 98%
“…91 Lm-activated signaling pathways in the neonate The particularly high risk of severe outcome from Lm infection in the newborn suggests that possible differences exist between the immune signaling pathways activated by Lm in neonates vs. the adult. 103,104 The importance of the MyD88-dependent pathway for host resistance is clearly seen from the extreme vulnerability displayed by MyD88-deficient mice to Lm infection. 105,106 Even though the ability for innate recognition of pathogens via the TLR/MyD88 pathway early in life does not appear to be different compared with adults, 107 there are stark contrasts between the downstream effector responses generated in the human newborn as compared with the young adult 103,104 (discussed in the following section).…”
Section: Lm-activated Signaling Pathwaysmentioning
confidence: 99%
“…The TLR/MyD88-dependent response of human neonatal monocytes specifically to Lm infection has yet to be explored. 104 While IRF3-dependent production of type I IFN via the STING/IRF3-dependent pathway in human newborns is reduced compared with adults, 103 the production of IFN-β in humans in response to Lm appears not IRF3-dependent but instead, p38 MAPK-dependent. 108 The role of the STING/IRF-3 pathway in human neonatal Lm infection is thus still unclear.…”
Section: Lm-activated Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations